Knowledge of Adults’ Reading Oral Cancer in South-East of Iran - Sara Amanpour; Maryam Raoof; Shahla Kakoei; Sorena Fardisi; Azadeh Iranmanesh; Molouk Torabi Parizi (International Journal of Epidemiologic Research, 2018)
Background and aims: Squamous cell carcinoma is one of the most common cancers in the oral cavity. The aim of this study was to assess the rate of awareness of people referring to medical clinics in Kerman because of the oral cancer and its risk factors from 2015 to 2016. Methods: This cross-sectional study was conducted on a sample size of 1200 subjects between April and December 2016 in Kerman, Iran. The participants were selected based on stratified sampling from dental clinics of 4 different areas of the city. After filling the informed consent form, they were asked to complete a self-administered questionnaire. The questionnaire included demographic information, awareness of subjects about common characteristics of oral cancer, and predisposing risk factors. To analyze the data, chi-square and analysis of variance (ANOVA) tests were used by means of SPSS 21.0. A value of P≤0.05 was considered to be significant. Results: A total of 58.8% of the participants showed intermediate level of knowledge regarding oral cancer. Knowledge about risk factors and symptoms was also at an intermediate level (57.2% and 65% respectively). Knowledge of women was significantly more than that of men (P=0.02). moreover, subjects who were married presented more correct answers than single ones (P=0.01). Moreover, urban dwellers were found to be more knowledgeable than rural populations (P=0.03). Conclusion: Although the public information on oral cancer is improving compared to a study carried out 7 years ago in Kerman, the level of knowledge is still not satisfactory. Indeed, much more efforts to increase public information by social media is needed